Public Perception of JKN Mobile Application Services (Study on Patients at Wajo Community Health Center) - Inayah Wulandari; Ansar Suherman; Wa Nurfida (Penerbit Jurnal Indonesia, 2024)
With the development of technology and information development that is very dynamic, the role of information technology applications as a means for the community without knowing the limits of time and place. so that it can meet the basic health needs of a decent society BPJS Health also utilizes technology to facilitate services and expand the scope of its membership. As of 2023 Mobile JKN has a total of 21,753,548 mobile users. Based on this description, the researcher tries to conduct a study to find out the extent of the community's view at the Wajo puskesmas on the JKN Mobile application service. This makes health services better known to the community Based on data from the e-puskesmas BPJS Health application specifically for PKM, the community's response at the wajo puskesmas to application services in mobile JKN is very easy when doing health services and administrative services.